The British Navy in Eastern Waters : the Indian and Pacific Oceans. - Grainger, John D. (Boydell & Brewer, Inc, 2022)
Provides a comprehensive overview of the activities of the British navy in the Indian and Pacific Oceans from the earliest times to the present.